PENGARUH LINGKUNGAN KERJA, GAYA KEPEMIMPINAN DAN MOTIVASI INTRINSIK TERHADAP KINERJA KARYAWAN CV. CIPTA MULYA, KABUPATEN MADIUN - Handoko, Nanang (Universitas Dr. Soetomo, 2023)
There are several factors that can affect employee performance, namely the work environment, leadership style and work motivation. The work environment is the conditions that exist around the workplace including aspects of temperature, lighting, air, sound and layout. Leadership style is one of the factors that can build a comfortable work environment. While work motivation is a condition that is formed from a sense of comfort in the work environment and leadership style so that employees are able to work well. The aim of this study was to determine the effect of the work environment, leadership style and work motivation on employee performance. The method used is a quantitative descriptive analysis method. The results of the study show that all factors that can influence employee performance have a positive effect. The existence of this research is expected to be able to show that aligning employee performance factors needs to be continuously developed in order to be able to improve employee performance. Because when employees work well, the company will be younger in achieving its vision and mission.